1999
DOI: 10.1108/09649429910301698
|View full text |Cite
|
Sign up to set email alerts
|

Sex equality in the financial services sector in Turkey and the UK

Abstract: In the UK and other western countries the financial services sector is seen as offering women better career prospects than most other sectors. Unprecedented numbers of well‐qualified young women are now achieving promotion to first‐line and middle management positions. Companies are represented as progressive employers, committed to promoting equal opportunities. However, a cross‐cultural study of three Turkish and six UK banks and high street financial organisations explores how organisational ideologies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 7 publications
1
33
0
2
Order By: Relevance
“…Male patterns of behaviour in networking is an example of subtle exclusion (Driscoll, 2004). The UK finance sector is a rather conspicuous example of the pervasively powerful and gender unequal effects a male culture can have on the careers of females (Woodward and Ozbilgin, 1999;Duncan, 2003).…”
Section: Inhibitorsmentioning
confidence: 98%
“…Male patterns of behaviour in networking is an example of subtle exclusion (Driscoll, 2004). The UK finance sector is a rather conspicuous example of the pervasively powerful and gender unequal effects a male culture can have on the careers of females (Woodward and Ozbilgin, 1999;Duncan, 2003).…”
Section: Inhibitorsmentioning
confidence: 98%
“…In the USA, Philp, et al (1992) note that women were more conservative investors than men, were less willing to commit their savings over long periods of time, and were less likely than men to purchase investments which have a highly variable rate of return. Women were also found to differ from men in their reasons for saving and investing (Hisrich and Ozturk, 1999), their patterns of ownership of financial assets (Woodward and Ozbiligin, 1999), and their use of financial planners (Devlin, 2002). In terms of bank choice criteria, Devlin (2002) found that women were significantly more likely to choose a bank that will provide them with a mortgage and will similarly choose a mortgage where they have another account, indicative of greater concurrent behavioural loyalty on the part of women.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Kemalist principles of republican secularism upheld the value of sex equality over and against a strong tradition of sex segregation originating from the Ottoman times (Öncü, 1981;Özkanli and Korkmaz, 2000). Legislation requiring sex equality in employment was rudimentary (Özbilgin, 2002;Woodward and Özbilgin, 1999), 2 but of critical importance was that the dominant ideologies of 'modernization' and 'westernization' gave priority to the elimination of overtly discriminatory policies and practices from the formal processes of public employment.…”
Section: Historical Forces and Women's Achievements In Turkeymentioning
confidence: 99%